Directory of NGOs for migrants in Asia. (Scalabrini Migration Center, 1997)
An initial, limited attempts to facilitate networking among organizations involved in assisting migrants in different countries. The directory is of composite nature, it comprises of NGOs, migrant associations, and sometimes affiliates of international organizations. The 147 organizations are arranged alphabetically by country and include information such as address, telephone numbers, contact persons, year founded, number of staff, and number of members, group served, purpose, service, major activities, publications, language, and networking associations. The directory also feature an index of service where the organizations are listed according to the services they provide.